PENGHAPUSAN PARKIR BERLANGGANAN DI BANGKALAN: SIMALAKAMA ANTARA POLITIK KEBIJAKAN DAN KEHILANGAN PENDAPATAN DAERAH - Maritza Aminatuzzuria; Alvin Naila; Aulia Safitri; Anida Naisyillatu Rohmah; Mohamad Djasuli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the impact of the abolition of the subscription parking policy in Bangkalan, which triggers a dilemma between fulfilling the aspirations of the community and the potential reduction in Regional Original Revenue (PAD). This study uses a qualitative method with a descriptive-analytical approach. The main data source used in this research is primary data obtained through direct observation and interviews with the parties involved, such as the Department of Transportation in Bangkalan Regency. The results show that the abolition of the subscription parking policy has dual consequences. On the one hand, this policy responds to public complaints against the practice of double levies by parking attendants. However, on the other hand, this policy has the potential to reduce the Regional Original Revenue (PAD) that was previously sourced from the subscription parking levy, which can have an impact on the regional development budget. The decision to abolish the subscription parking policy illustrates the challenges in formulating public policies that must balance the interests of the public and the financial sustainability of the region. This research recommends a more transparent and systematic parking management mechanism to reduce illegal levies and maintain the stability of local revenue. This study provides insights into the dynamics of public policy in the context of parking governance in the region, as well as offering new perspectives in finding equitable and sustainable solutions for local governments and communities, because until now there have not been many studies that specifically examine the issue in depth, especially in the local context.